Vertical split fracture of the vertebral body following oblique lumbar interbody fusion: A case report. Issue 21 (27th May 2022) - Hong, Jong-Hwan; Han, Moon-Soo; Lee, Jung-Kil; Moon, Bong Ju
Abstract: Rationale: Oblique lumbar interbody fusion (OLIF) is an effective and safe surgical technique widely used for treating spondylolisthesis; however, its use is controversial because of several associated complications, including endplate injury. We report a rare vertebral body fracture following OLIF in a patient with poor bone quality. Patient concerns: A 72-year-old male patient visited our clinic for 2 years with lower back pain, leg radiating pain, and intermittent neurogenic claudication. Diagnoses: Lumbar magnetic resonance imaging revealed L4-5 stenosis. Intervention: We performed OLIF with percutaneous pedicle screw fixation and L4 subtotal decompressive laminectomy. We resected the anterior longitudinal ligament partially for anterior column release and inserted a huge cage to maximize segmental lordosis. No complications during and after the operation were observed. Further, the radiating pain and back pain improved, and the patient was discharged. Two weeks after the operation, the patient visited the outpatient department complaining of sudden recurred pain, which occurred while going to the bathroom. Radiography and computed tomography revealed a split fracture of the L5 body and an anterior cage displacement. In revision of OLIF, we removed the dislocated cage and filled the bone cement between the anterior longitudinal ligament and empty disc space. Further, we performed posterior lumbar interbody fusion L4-5, and the screw was extended to S1. Outcomes: After the second surgery, back pain and radiating pain in the left leg improved, and he was discharged without complications. Lesson: In this case, owing to insufficient intervertebral space during L4-5 OLIF, a huge cage was used to achieve sufficient segmental lordosis after anterior column release, but a vertebral body coronal fracture occurred. In patients with poor bone quality and less flexibility, a huge cage and over-distraction could cause a vertebral fracture; hence, selecting an appropriate cage or considering a posterior approach is recommended.